DEVELOP TEACHERS' VISION AND MISSION AS CHANGE AND CHARACTER EDUCATION - Avaset Berangaria (Sensei International Journal of Education and Linguistic, 2021)
The main indicator of a superior school is reflected in the teacher quality factor. Teachers are required to have professionalism in their field. Not only do they have to have knowledge about the field they teach, but all components related to education must exist in each teacher. This is also based on the assumption that the problem of improving the quality of education is certainly based on the character of an educator. Therefore, the more qualified teachers in a school, the more qualified the school will be. Teachers are expected to equip their students as the successors of this nation. Of course, by giving birth to individuals who not only have intellectual abilities, but are also able to appreciate truth, justice, prosperity, peace and a responsible attitude to enter a future era that is highly competitive and without limits. A big dream for this nation which is certainly not just a mere utopia, but we all have to be able to make it happen. Thus, the future of this country depends on how teachers can produce individuals who are independent, mature, responsible and sensitive to social problems in their surroundings in the future.